Wireless Internet Mobility - Misita Anwar (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
The ubiquotus internet use together with the proliferation of wireless devices such as pdas, laptops and palmtops has triggered the need of wireless internet mobility. However there are several challenges that need to be address to be able to support mobility. This report highlights several problem in supporting host mobility and propose solutions in the literatures to concludes on the most efficient way in achieving seamless user mobility without suffering too much from degraded quality of services.Keywords: internet mobility, mobile ip, wireless